Helical mesoscopic crystals based on an achiral charge-transfer complex with controllable untwisting/breaking. Issue 78 (10th September 2021) - Yang, Canglei; Luo, Lixing; Chen, Jinqiu; Yang, Bo; Wang, Wei; Wang, Hebin; Long, Guankui; Liu, Guangfeng; Zhang, Jing; Huang, Wei
Abstract : The donor and acceptor molecules self-assemble into a helical morphology under the effect of polar solvent. By controlling the temperature to induce phase transition, the co-crystal undergoes predictable crystal breaking or untwisting. Abstract : The development of synthetic helical structures from achiral molecules and stimulus-responsive shape transformations are vital for biomimetics and mechanical actuators. A stimulus regarded as the force to induce chirality modulation plays a significant role in the helical supramolecular structure design through symmetry breaking. Herein, we synthesized a metastable complex Form 1 crystal composed of pyrene and (4, 8-bis(dicyanomethylene)-4, 8-dihydrobenzo[1, 2- b :4, 5- b ′]-dithiophen-e) DTTCNQ components with a torsional backbone by C–H⋯N hydrogen bonds via a quick cooling method. The helix motion kinetics of Form 1 depends on the intrinsic factor (crystal thickness) and external stimuli (polar solvents). The self-assembled helical microstructures grow into needle-like crystals in liquid media via an untwistingprocess. Furthermore, they undergo predictable deformation of untwisting or breaking under a stimulus-responsive strain-relaxing phase transformation. This work illustrates a new approach in the mediated formation of helical morphologies from achiral binary supramolecules and dynamic motion, which is vital for biomimetics and mechanical actuators.